Tuberculosis-Associated HLH in an 8-Month-Old Infant: A Case Report and Review - Hauch, Holger; Skrzypek, Susanne; Woessmann, Wilhelm; Lehmberg, Kai; Ehl, Stephan; Speckmann, Carsten; Schneck, Emmanuel; Koerholz, Dieter; Jux, Christian; Neuhäuser, Christoph (Frontiers in Pediatrics, 2020)
Hemophagocytic lymphohistiocytosis (HLH) is a rare immunological disease, which can be mistaken for sepsis easily. Among the infectious causes that may trigger secondary HLH, tuberculosis (TBC), a rather rare pathogen nowadays, is typical. To our knowledge, this is the first case report of an infant suffering from TBC-associated HLH-induced acute respiratory failure who was treated successfully using extracorporeal membrane oxygenation. An 8-month-old boy with fever (over the last 8 wk) and pancytopenia was transferred to our institution with acute respiratory failure and for extracorporeal membrane oxygenation therapy. Bone marrow biopsy revealed hemophagocytosis. Immunological work-up for familial HLH was negative. In a desperate search for the cause of secondary HLH, an interferon-gamma release assay for TBC returned positive. However, microscopy for acid-fast bacteria as well as polymerase chain reaction for TBC were initially negative. Despite this, the child was treated with tuberculostatic therapy. TBC was finally confirmed. The child remained on extracorporeal membrane oxygenation for 28 d. Further work-up showed typical lesions of disseminated TBC. The mother was identified as the source of TBC. The boy presents with mild sequelae (fine motor skills). In infants with suspected septicemia, TBC should be considered as differential diagnosis even if the results are initially negative.